Robust Evaluation Model Analysis of Decision Support System in Warehouse Selection Based on Multi-Criteria Decision Making and Sensitivity Analysis - syukriah syukriah; Defi Irwansyah; Lis Ayu Widari; Mutamimmul Ula; Veri Ilhadi (Universitas Malikussaleh, 2026)
Determining strategic warehouse locations is complex because it involves various criteria that are often conflicting, such as cost, ease of access, capacity, and operational risk. This study aims to evaluate a robust model in a Decision Support System (DSS) for warehouse selection using a Multi-Criteria Decision Making (MCDM) approach. The applied methodology combines several MCDM techniques, namely the Analytical Hierarchy Process (AHP) to determine the criteria weights and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) to rank alternatives. In addition, a sensitivity analysis is used to test the level of stability and resilience of the model to changes in criteria weights. The results show that the developed model is able to produce stable and responsive recommendations to variations in decision parameters. The sensitivity analysis also reveals that several criteria have a significant influence on the final result, thus requiring more attention in the weighting process.